Exploratory Factor Analysis of Environmental Awareness Assessment based on Local Wisdom by Using Summated Rating and Likert Scale - Wusqo, Indah Urwatin; Setiawati, Farida Agus; Istiyono, Edi; Mukhson, Ali (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2022)
There is no standardized instrument to measure environmental awareness based on local wisdom. Therefore, the purpose of this study is to conduct an Exploratory factor analysis (EFA) on an environmental awareness assessment based on local wisdom. This study has a non-experimental design with the ex-post facto type. The Likert scale environmental awareness is transformed into a summated rating scale. Furthermore, the initial construct validation was carried out using the EFA test. Based on the results of the EFA, it was found that the EA which previously consisted of 18 indicators extracted based on eigen values and fixed factors became 8 factors with 14 indicators.